2009
DOI: 10.1002/adma.200801650
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Thienothiophene Copolymers: Design, Synthesis, Morphology, and Performance in Thin‐Film Organic Transistors

Abstract: Organic semiconductors are emerging as a viable alternative to amorphous silicon in a range of thin‐film transistor devices. With the possibility to formulate these p‐type materials as inks and subsequently print into patterned devices, organic‐based transistors offer significant commercial advantages for manufacture, with initial applications such as low performance displays and simple logic being envisaged. Previous limitations of both air stability and electrical performance are now being overcome with a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
373
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 411 publications
(391 citation statements)
references
References 91 publications
15
373
0
3
Order By: Relevance
“…Initial studies have focussed upon blends of PCBM with poly(2,5-Bis(3-alkylThiophen-2-yl)Thieno[3,2-b]Thiophene) (pBTTT), which is an alternating co-polymer of thieno-[3,2-b]thiophene and 4,4-dialkyl 2,2-bithiophene repeat units. 36 The reduced sidechain density of pBTTT compared to P3HT facilitates the formation of highly ordered thin film structures, which are driven by interdigitation of the alkyl sidechains of adjacent polymer backbone.…”
Section: Side Chain Densitymentioning
confidence: 99%
“…Initial studies have focussed upon blends of PCBM with poly(2,5-Bis(3-alkylThiophen-2-yl)Thieno[3,2-b]Thiophene) (pBTTT), which is an alternating co-polymer of thieno-[3,2-b]thiophene and 4,4-dialkyl 2,2-bithiophene repeat units. 36 The reduced sidechain density of pBTTT compared to P3HT facilitates the formation of highly ordered thin film structures, which are driven by interdigitation of the alkyl sidechains of adjacent polymer backbone.…”
Section: Side Chain Densitymentioning
confidence: 99%
“…[5][6][7][8][9][10] A number of recent studies have demonstrated that molecular ordering along the polymer backbone and between chains is far more important to carrier transport in high molecular weight (Mw) polymer films than domain boundaries. [11][12][13][14][15][16] However, high Mw semi-flexible polymers are thought to be difficult to push into a highly molecularly ordered state due to entanglements and interactions which can inhibit molecular diffusion and challenge conformational transitions.…”
Section: Introductionmentioning
confidence: 99%
“…32) Regarding low-molecular-weight organic semiconductors compatible with coating processes, a mobility of approximately 1 cm 2 V À1 s À1 has been reported for various materials, such as triisopropylsilylethynyl (TIPS) pentacene 33) and porphyrin- 34) and benzothienobenzothiophene (BTBT) 35) -based materials. Regarding polymers, a mobility of 0.5 cm 2 V À1 s À1 was achieved for thiophene-based polymers using crystalline materials, 36) and a mobility of 1 cm 2 V À1 s À1 was achieved for transistors fabricated by solution processing. 37) Many organic semiconductors, including not only p-type but also n-type organic semiconductors, have been reported because of the great diversity of organic compounds.…”
Section: Solution-processable Semiconductorsmentioning
confidence: 99%
“…However, the degradation in the performance of p-type low-molecular-weight semiconductors due to atmospheric exposure has been reduced to a negligible level owing to recent progress in material technologies. [32][33][34][35][36][37][38][39][40][41]99,100) In the future, improved electrical characteristics, reliability, and stability will also be required for highly soluble semiconductors; the performance and stability of these organic semiconductors depend on the combination of insulating layers and electrodes used in the transistor structures. Namely, it is necessary to further enhance the compatibility among insulating layers, semiconductors, and electrodes by controlling their interfaces to realize higher stability.…”
Section: Large-area Actuatorsmentioning
confidence: 99%